Modern concepts of the mycosis fungoides pathogenesis - A. A. Vorontsova; A. E. Karamova; L. F. Znamenskaya (Онкогематология, 2018)
Mycosis fungoides – the most common form of cutaneous T-cell lymphoma. The pathogenesis of this disease is complex and remains unclear. The article contains a review of the literature devoted to the main mechanisms of T-lymphocytes malignant proliferation, known to date. Data on dysregulation of immune, genetic and epigenetic mechanisms, as well as the role of microenvironment cells in the proliferation of T lymphocytes, are given. Immunophenotypic characteristics and cellular composition of the infiltrate in patients with mycosis fungoides, are described depending on the stage of the disease. Prospective directions in studying molecular-biological predictors of malignant lymphoproliferative diseases development are highlighted.